Characterization & Separation Of Tungsten In Cassiterite (Tin Middling) From Bukit Kachi Mine - Nor Asim, Muhammad Danial Haziq (Universiti Sains Malaysia, 2022)
This study covers characterization and separation of tungsten in by using mozley table, magnetic separator and high tension roll separator (HTRS). This research aims to characterize the sample and get the high recovery of tungsten by separating the tungsten in cassiterite (tin middling)which contain 40% and 60% tungsten in cassiterite from Bukit Kachi Mine. Firstly, the visual observation, microscopic analysis, XRD analysis, and XRF analysis were carried out on the raw sample at the initial stage of investigation. The XRF analysis results, indicated that the most valuable minerals are casssiterite, hematite and wolframite for Sample A1 and B1 . The raw samples were separated by using a mozley table and produced two products: high specific density and low specific density. After the mozley table process are completed, the high specific density samples undergo the magnetic separator and produce two products which are magnetic and non-magnetic. Lastly, after the magnetic process is completed, the magnetic samples undergo the HTRS and produce two products which are conductor and non-conductor. Sample from every physical process required undergoes the grinding method since SEM-EDX observation shows there is mineral interlock with other minerals. The ring mill was chosen to reduce the size of samples, and the results were subjected to XRF and XRD analysis. From XRF and XRD results, we know that it successfully separates tungsten from cassiterite and from each process we can see that the recovery tungsten (WO₃) in the sample increases which is 72.03% for Sample A1 and 38.89% for sample B1.